DOZ047.103: Learning curve and long-term outcomes for jejunal replacement of the esophagus: a single-center experience in the pediatric population. (24th June 2019) - Svetanoff, W J; Zendejas, B; Bairdain, S; Hernandez, K; Davidson, K; Hamilton, T E; Ngo, P; Manfredi, M; Smithers, C J; Jennings, R W
Abstract: Introduction: Patients with complex esophageal atresia (EA) may require replacement; jejunal interposition is an option that is uncommon in children. This study aimed to identify the procedural learning curve and outcomes of patients undergoing jejunal interposition. Methods: In a retrospective analysis, patients were divided into those who had surgery between 2010 and 2015 (incipient cohort–previously reported) and those who underwent surgery between 2016 and 2018 (contemporary cohort). Outcomes included length of paralysis (LOP), time to extubation, length of stay (LOS), and complication rate. Current feeding status and time to full oral intake were recorded. Mann–Whitney U and Fisher's exact tests were used for analysis. Results: The cohort included 13 in the incipient group and 40 in the contemporary group. LOP (5.33 vs 1.88 days, P = 0.002), time to extubation (9.50 vs 6.34 days, P = 0.05), ICU stay (54 vs 12.65 days, P = 0.04), and LOS (86.77 vs 32.90 days, P = 0.003) were shorter in the contemporary cohort. The complication rate was similar between the incipient and contemporary cohorts, respectively (69.23% vs 50%, P = 0.231). Fourteen patients (incipient–6, contemporary–8) reached full oral intake by a median follow-up of 6.35 months (0.36–26.63 months); another 23 have consistent oral intake but require some use of a feeding tube. All can handle secretions. Patients who had oral intake preoperatively, even with an esophagostomy, were more likely to be eating all consistencies postoperatively (67.74% vs 27.30%, P = 0.004). Conclusion: As our experience has improved, LOP, intubation time, and LOS have decreased. Preoperative oral intake, even if sham feeding, was a significant determinant for consistent oral intake postoperatively.